The professional wild food community and Covid-19: The use of online platforms in supporting people to access alternative food sources. Issue 2 (2nd July 2020) - Townsend, Leanne
ABSTRACT: This paper reflects on the response of the professional wild food community in the United Kingdom to lockdown measures during Covid-19. It explores the rapid adaptation of the community toward providing (mostly free of charge) online support via various social media platforms and using various communication tools. This support is aimed at providing high quality information on how to safely forage for wild foods in rural and urban environments. The paper considers the reasons for increased interest amongst the general public in foraging for wild foods during Covid-19. It reflects on motivations for wild food professionals to provide free online education, and the longer-term impacts on their economic viability once lockdown has been lifted, considering bridging social capital as one positive outcome of these support activities. It frames wild food as an alternative local food system with potential for increasing the resilience of local communities in times of uncertainty.